Smart Grid Functioning of Solar Electric System Network Based on Complex Accumulation Control (Journal of Solar Energy Research Updates, 2023)
Abstract: Voltage maintenance in the distribution system takes place with the use of additional devices. The purpose of the work is to develop a Smart Grid functioning of the solar electric system network based on integrated storage control. Accumulator battery and thermoelectric accumulator as part of the solar electric system network acquire the additional status of voltage regulators in the distribution system. A comprehensive integrated system has been developed for supporting the functioning of the solar electric system network based on a prediction of changes in the battery capacity and power factor. Advanced decisions on change the capacity of the thermoelectric accumulator in redistributes the accumulated electrical energy. Changing the level of transmission of electric energy to the network make it possible to maintain voltage in the distribution system through maintaining the power factor of the network solar electric system. Continuous measurement of the voltage at the input to the hybrid inverter, the voltage at the output from the frequency converter and in the distribution system takes place. The change in the ratio of voltage at the output of the frequency converter and in the distribution system is evaluated. The peak load of the energy system is prevented, reducing the consumption of energy from the network to 14%.